Developing Digital Modules Based On Audio PPT Equation Tangent Circle Using Geogebra Application - Maharani Arista Putri (Publikasi Indonesia, 2023)
The study aimed to develop GeoGebra-based interactive GeoGebra-based course modules and validate them using expert assessment. The research method used in this study is a research and development method using a 4-D approach. This approach includes four stages, namely Define, Design, Develop, and Disseminate. This research was conducted at MTs PKP and the development research time was carried out from January to March 2023. The results of this study show excellent module quality in aspects of content feasibility, learning quality, display quality, visual clarity, material presentation, language, use of GeoGebra, and visual skills. Trials for teachers and students also produced positive responses, with a very good percentage of success.